A Model for Successful Professional Learning Communities to Meet the Requirement of Vietnam Education Reform - Hai, Pham Thi Thanh; Linh, Doan Nguyen; Kusakabe, Tatsuya (VNU Journal of Science: Education Research; Vol 37 No 4, 2021)
Teachers working in rural areas need professional and teaching skills support. This study was conducted at the Lower Secondary School in Hanoi, Vietnam. This research introduces the policy of Professional Learning Communities to the teachers and it’s a practice at school. This paper shows a model to implement policies regarding the professional development of teachers at school. The results show that the school runs a good model of professional learning communities such as directing the development and implementation of school education plans and professional training activities. Professional Learning Communities is the target of the teachers at school developing teaching profession.